Temperature Distribution Research on Liquid Packaging Structure of Deep UV LEDs - Zhenghao Xia; Zuojie Wen; Bingqian Li; Fei Wang; Daming Zhang (International Journal of Photoenergy)
By showing a packaged device model with 2×2 chips, the effects of packaging material, device height, chip spacing, thermal conductivity, and viscosity of silicone oil on temperature distribution of deep ultraviolet (UV) light-emitting diodes (LEDs) were investigated by finite element simulation. The results showed that similar temperature distributions in the horizontal and vertical directions were obtained using different packaging materials including gas, solid, and liquid. The lowest maximum temperature (131.7°C) was obtained with liquid packaging compared to the gas packaging (140.8°C) and solid packing (132.5°C). Accompanied by increasing the device height, the maximum temperature of the liquid packaging structure revealed a more significant drop compared to solid packaging. However, that of gas packaging exhibited a rise and saturation. Larger chip spacing and higher thermal conductivity of silicone oil will dramatically reduce the maximum temperature of the liquid packaging device, and a lower maximum temperature and more uniform temperature distribution were obtained by using a lower viscosity packaging material. Therefore, considering the feasibility of the device process, appropriate liquid packaging structures can be optimized, and the maximum temperature of the liquid packaging structure of 102.8°C has been achieved. Liquid packaging may have a certain impact on the reliability of device sealing due to the current immature technology. For high-power light sources, there may also be a certain impact on their lifespan.